The Depiction of Spain in Eugen Ruge’s Travel Novel "Cabo de Gata" - Bies, Andrea (Revista de Filología Alemana, 2016)
In the following article I analyse the depiction of Spain in Cabo de Gata (2013), a work belonging to the genre of the travel novel. In so doing, I draw attention to a genre that has received little attention in the research of the image of Spain in German travel literature. This consideration focuses on the travel motif as well as the perception and representation of Spain as a foreign country. Narratological analysis of selected aspects of the narrative technique diminishes the imagological impact of the novel.
Keywords: Ruge; Image of Spain; Travel literature; Perception of the other; Narratology